Pachydermodactyly presenting as juvenile idiopathic arthritis in an adolescent man. Issue 1 (18th January 2021) - Jubber, Ameen; Gnanappiragasam, Dushyanth; Durrani, Maumer; Kinder, Alison; Harman, Karen E
Abstract : We present the case of a 17-year-old Asian man diagnosed with pachydermodactyly, a rare digital fibromatosis. Although this is a non-inflammatory periarticular soft tissue disorder, the clinical appearance can mimic inflammatory arthritis. The patient had a 2-year history of fusiform swelling of multiple proximal interphalangeal joints. He was initially diagnosed with juvenile idiopathic arthritis and treated with methotrexate, but a lack of clinical response led to the diagnosis of pachydermodactyly. Recognising this rare condition can prevent unnecessary and potentially harmful treatment.